A NEW SPECIES OF ZINGIBER (ZINGIBERACEAE) FROM ENGGANO ISLAND, INDONESIA - ARDIYANI, MARLINA (Research Center for Biology, 2015)
ARDIYANI, M. 2015. - A new species of Zingiber (Zingiberaceae) from Enggano Island, Indonesia. Reinwardtia 14 (2): 307 - 310. - A species of Zingiber Miller (Zingiberaceae), Z. engganoensis Ardiyani, from Enggano Island, Indonesia is described. The species is only known from its type locality. It is similar to Z. spectabile Griff. but with some morphological differences. Three-locus DNA barcodes (rbcL, matK and ITS2) of the new species were generated for its identification purposes